Monte carlo simulation of different source configurations for a new design of rotating Gamma Knife system. (September 2016) - Mora, G.; Chivani, O.; Li, J.; Ma, C.M.
Abstract : Introduction: A new design of Gamma Knife consist of 30 60 C0 source capsules, two circular primary collimators (diameter of 6.60 mm and 6.10 mm) and four different changeable collimators. The sources (diameter of 2.8 mm) are distributed in six groups of five sources in the spherical geometry. Each source is individually collimated to obtain four different circular fields at the isocenter (3 mm, 3.5 mm, 6 mm and 8 mm). Purpose: To determine the characteristics of the Co 60 beam emerging from a new design of Gamma Knife system and to calculate dose distributions at the isocenter distance for different source configurations and collimator openings Materials and methods: We have used the BEAM-Monte Carlo code to realistically model the geometry design, including source capsules, primary and secondary collimators. The shielding of the head was also simulated. The dose distributions at the isocenter distance are calculated using GEPTS in a previous designed spherical component module for the circular field sizes studied. Results: The spectra of particles emerging from each source-collimator configuration is calculated.The radial photon fluence does not vary significantly inside the collimator openings. The spectra of particles from different source groups are compared. Conclusion: The 60 Co beam emerging from each group source configuration was characterized but our preliminary results do not allow to properly determine the variation of spectra of particles at isocenter as function of source group position. Further investigations are needed.